The Role of Mitonuclear Incompatibility in Bipolar Disorder Susceptibility and Resilience Against Environmental Stressors - Gonzalez, Suzanne (Frontiers in Genetics, 2021)
It has long been postulated that mitochondrial dysfunction plays a key role in the etiology of bipolar disorder (BD). Mitochondrial functioning plays an important role in regulating synaptic transmission, brain function, and cognition. Neuronal activity is energy dependent and neurons are particularly sensitive to changes in bioenergetic fluctuations, suggesting that mitochondria regulate fundamental aspects of brain function. There is robust evidence supporting mitochondrial dysfunction in the pathophysiology of BD including impaired oxidative phosphorylation, general decrease of energy, impaired energy metabolism in the brain, co-morbidity with mitochondrial diseases, and association with genetic variants in mitochondrial DNA (mtDNA) or nuclear-encoded mitochondrial genes. Despite these advances, the underlying etiology of mitochondrial dysfunction in BD is unclear. A plausible evolutionary explanation is that mitonuclear incompatibility leads to a desynchronization of machinery required for efficient electron transport and cellular energy production. Approximately 1200 genes, encoded from both nuclear and mitochondrial genomes, are essential for mitochondrial function. Studies suggest that mitochondrial and nuclear genomes co-evolve, and the coordinated expression of these interacting gene products are essential for optimal organism function. Incompatibilities between mtDNA and nuclear‐encoded mitochondrial genes results in inefficiency in electron flow down the respiratory chain, differential oxidative phosphorylation efficiency, increased release of free radicals, altered intracellular Ca2+ signaling, and reduction of catalytic sites and ATP production. This review explores the role of mitonuclear incompatibility in BD susceptibility and resilience against environmental stressors.